1984
DOI: 10.1073/pnas.81.9.2878
|View full text |Cite
|
Sign up to set email alerts
|

Nondisulfide polymerization of gamma- and beta-crystallins in the human lens.

Abstract: The water-soluble 43,000-dalton fraction (WS43) of the human lens has been shown to be heterogeneous. It appears to contain, in addition to actin, components related to the crystallins. Immunoblot reactions indicate that this polypeptide fraction is composed of dimers containing (iand y-crystallin components. It has been estimated that 10-30% of this fraction arises by dimerization of y-crystallin. A possible route for the formation of the 43,000-dalton fraction is suggested by the observation that photolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Laminin and fibronectin eluted from the gel close to the void volume, and these two components were separated from the laterlished the preduminantly noncollagenous character of emerging entactin peak (Kav = 0.30). The P-crystallin, guanidine HCl-extractable proteins and were consistent as anticipated (Roy et al, 1984), appeared as a well with their amino acid composition.…”
Section: Fractionation Of Guanidine Hc1-extracted Proteinsmentioning
confidence: 55%
“…Laminin and fibronectin eluted from the gel close to the void volume, and these two components were separated from the laterlished the preduminantly noncollagenous character of emerging entactin peak (Kav = 0.30). The P-crystallin, guanidine HCl-extractable proteins and were consistent as anticipated (Roy et al, 1984), appeared as a well with their amino acid composition.…”
Section: Fractionation Of Guanidine Hc1-extracted Proteinsmentioning
confidence: 55%
“…The formation of disulfide-crosslinked high molecular weight aggregates, as observed in this study, is a common feature of oxidatively damaged cytoskeletal proteins Graceffa, Adam and Lehman, 1993 ;Schwartz et al, 1987 ;Zaremba et al, 1984). Lens epithelial cells which have been exposed to sulfhydryl oxidants such as H # O # or diamide suffer a severe disruption of cytoskeletal protein organization (Ikebe et al, 1989 ;Prescott et al, 1991), and cytoskeletal components have been reported to be present in the high molecular weight aggregated protein of human senile cataracts (Roy et al, 1984). Two recent studies using oxidative models for cataract in vivo (buthionine sulfoxamine cataract in the mouse and selenite cataract in the rat) have also demonstrated a heightened loss of lens cytoskeletal proteins in the early stages of cataract (Calvin et al, 1992 ;Matsushima et al, 1997).…”
Section: Discussionmentioning
confidence: 78%
“…1989; as well as disulfide and non-disulfide covalent cross-linking (Fujimori, 1982;Gossey et al, 1980;Dillon et al, 1985;Roy et al, 1984;Saito & Matsuura, 1985, Schiavon & Veronese, 1986; Borkman et al, 1986). As a result of various therapies and diseases, metabolites such as porphyrins, which are efficient photosensitizers, can reach the eye (Kessel et al, 1987;Fraunfelder, 1982).…”
mentioning
confidence: 99%